Recent Progress on NIR-II Photothermal Therapy - Zhang, Yunguang; Zhang, Siyu; Zhang, Zihan; Ji, Lingling; Zhang, Jiamei; Wang, Qihao; Guo, Tian; Ni, Simin; Cai, Ru; Mu, Xiaoyu; Long, Wei; Wang, Hao (Frontiers in Chemistry, 2021)
Photothermal therapy is a very promising treatment method in the field of cancer therapy. The photothermal nanomaterials in near-infrared region (NIR-I, 750-900 nm) attracts extensive attention in recent years because of the good biological penetration of NIR light. However, the penetration depth is still not enough for solid tumors due to high tissue scattering. The light in the second near-infrared region (NIR-II, 1000-1700 nm) allows deeper tissue penetration, higher upper limit of radiation and greater tissue tolerance than that in the NIR-I, and it shows greater application potential in photothermal conversion. This review summarizes the photothermal properties of Au nanomaterials, two-dimensional materials, metal oxide sulfides and polymers in the NIR-II and their application prospects in photothermal therapy. It will arouse the interest of scientists in the field of cancer treatment as well as nanomedicine.